Revel rising an affinity-generative fan experience facility for the P-pop music industry - Baynosa, Niel Alfred T.; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
P-pop, an emerging form of Filipino popular music, has been responding to the increased interest of Filipinos in globally-successful music genres. The further development of P-pop as a means of leveraging soft power for geopolitical advantage has been identified in several studies. These studies recognize the benefits of developing P-pop as both a media product and cultural industry, enhancing national identity, cultural expression, and international recognition of Filipino talent. However, the question of how to develop the industry and cultivate the increasing support it currently garners from fans and casual listeners remains unanswered. This question presents an opportunity to address the architectural experiences. An architectural solution is proposed through this comprehensive design project, creating Revel Rising, a fan experience facility for P-pop music. Revel Rising aims to generate and cultivate support for P-pop by meeting fans' spatial needs and desired experiences. The facility derives architectural design concepts from fans' perceived interest in P-pop music, idols, and cultural content. Designed to enhance the overall P-pop music, idols, and cultural content. Designed to enhance the overall P-pop fan experience, Revel Rising incorporates food, retail, recreational, and congregation spaces, all designed through the following architectural design concepts: captivating, versatile, and resonant.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Music industry; Popular music fans; Popular music